hiv and vulnerability: a comparison of three groups in Cali, Colombia - Jaime Galindo Q; Inés C. Tello B; Héctor F. Mueses M; Jorge E. Duque M; Gail Shor-Posne; Geraldine Moren (Universidad de Antioquia, 2011)
Objetive: to identify socio-demographical characteristics and risk behaviors for hiv /Aids and hiv status in three groups of participants from different socio-economic background in Cali. Methodology: between 2005 and 2007, an active sur-veillance campaigns was done and included 4055 voluntary participants who gave informed consent, answered a structured questionnaire, and received pre- and post-test counseling and hiv testing. The participants were grouped in three categories: a total of 1217 from low socio-economic status (lse), with low education and high unemployment (N1), 899 employed workers with technical-professional schooling and upper-middle socio-economic status (N2), and 1939 students of private universities and upper-middle socio-economic status (N3). Socio-demographic characteristics, sexual behaviors and hiv knowledge self-perception were assessed. Statistical analyses: Chi Square, and independent T tests with significance <0.05, 95% confidence intervals. Results: overall prevalence of hiv was 0.62%; in the N1 group prevalence was 1.97%, significantly higher than in the other two groups, (p<0.0001). Conclusions: a higher prevalence of hiv in the N1 (lse) group was evident, along with a more frequent history of previous Sexual Transmision Disease (std), and poorer self-perception of hiv knowledge, highlighting the need to strengthen std and hiv prevention and testing strategies targeting this group.